POPULATION DYNAMICS OF THE MAIN PELAGIC SPECIES EXPLOITED IN THE JAVA SEA: BIOLOGICAL PARAMETERS ESTIMATES - Bambang Sadhotomo (Indonesian Fisheries Research Journal, 2006)
several sets of length frequency data (1991 to 1995) of the six species were used to estimate the growth parameters and to discuss the results in relation to possible influence of data structure on the parameter estimates